Unveiling ‘Spek LC’: How Language Perpetuates Gender Bias through Digital Discourse - Puji Aishya Daffani; Dhuha Hadiyansyah (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
Language plays a central role in shaping and reproducing social reality. Through language, individuals construct meaning, express ideology, and reinforce or challenge social hierarchies. One expression that illustrates this dynamic is “Spek LC”, a popular term on social media on platform X. Derived from “spek” (specification) and “LC” (Lady Companion), it originally described physical looks but has shifted into a form of verbal violence and gender-based discrimination against women. This study analyzes the denotative and connotative meanings of “Spek LC” and its psycholinguistic implications using Roland Barthes’ (1957) connotative semiotics and the Affective Load framework. Employing a qualitative content analysis, textual data were collected from public posts and comments containing the term “Spek LC” on platform X. Findings reveal that at the denotative level, the term refers to appearance, while at the connotative level, it functions as a derogatory label suggesting immorality and social inferiority. Exposure to this term generates a high affective load, evoking emotions such as shame, anger, and self-stigmatization. Overall, the study shows that language in social media operates as a symbolic power that perpetuates gender bias through emotional and ideological mechanisms. It emphasizes the need for critical language awareness to promote ethical and inclusive digital communication.Keywords: Connotative Semiotics, Digital Verbal Violence, Gender Based Discrimination.